Chemical Enhancer: A Simplistic Way to Modulate Barrier Function of the Stratum Corneum - Tasnuva Haque; Md Mesbah Uddin Talukder (Tabriz University of Medical Sciences, 2018)
Human skin could be a prime target to deliver drugs into the human body as it is the largest organ of human body. However, the main challenge of delivering drug into the skin is the stratum corneum (SC), the outer layer of epidermis, which performs the main barrier function of the skin. Scientists have developed several techniques to overcome the barrier properties of the skin, which include other physical and chemical techniques. The most common and convenient technique is to use special formulation additives (chemical enhancers, CEs) which either drags the drug molecule along with it or make changes in the SC structure, thereby allowing the drug molecule to penetrate in to the SC. The main focus is to deliver drugs in the certain layers of the skin (for topical delivery) or ensuring proper percutaneous absorption (for transdermal delivery). However, skin drug delivery is still very challenging as different CEs act in different ways on the skin and they have different types of interaction with different drugs. Therefore, proper understanding on the mechanism of action of CE is mandatory. In this article, the effect of several CEs on skin has been reviewed based on the published articles. The main aim is to compile the recent knowledge on skin-CE interaction in order to design a topical and transdermal formulation efficiently. A properly designed formulation would help the drug either to deposit into the target layer or to cross the barrier membrane to reach the systemic circulation.